2021
DOI: 10.1001/jamaneurol.2021.1312
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Neuroimaging Biomarkers Across Disease Stage in Parkinson Disease

Abstract: Imaging biomarkers in Parkinson disease (PD) are increasingly important for monitoring progression in clinical trials and also have the potential to improve clinical care and management. This Review addresses a critical need to make clear the temporal relevance for diagnostic and progression imaging biomarkers to be used by clinicians and researchers over the clinical course of PD. Magnetic resonance imaging (diffusion imaging, neuromelanin-sensitive imaging, iron-sensitive imaging, T1-weighted imaging), posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 109 publications
1
64
1
1
Order By: Relevance
“…Thus, it is likely that corpus callosum neurodegeneration is associated with even more advanced and severe Parkinsonism. We did not detect progression effects in the substantia nigra with any diffusion method which has been previously found in the posterior substantia nigra in early PD and anterior substantia nigra in moderate- to late-stage PD ( Mitchell et al, 2021 ). In the current cohort, we did find elevated FW and Viso in the posterior substantia nigra of PD cross-sectionally compared with controls, and thus it is most likely that extracellular fluid had already increased to a plateau and the 1-year time frame used here was not sufficient for the more advanced disease stage of this PD cohort (4.5 years).…”
Section: Discussioncontrasting
confidence: 42%
“…Thus, it is likely that corpus callosum neurodegeneration is associated with even more advanced and severe Parkinsonism. We did not detect progression effects in the substantia nigra with any diffusion method which has been previously found in the posterior substantia nigra in early PD and anterior substantia nigra in moderate- to late-stage PD ( Mitchell et al, 2021 ). In the current cohort, we did find elevated FW and Viso in the posterior substantia nigra of PD cross-sectionally compared with controls, and thus it is most likely that extracellular fluid had already increased to a plateau and the 1-year time frame used here was not sufficient for the more advanced disease stage of this PD cohort (4.5 years).…”
Section: Discussioncontrasting
confidence: 42%
“…Biomarkers play an important role in the evaluation of the onset of chronic diseases as well as in the development of drug treatments for these conditions ( 36 ). Biomarkers may also be able to reflect the pathophysiological process of a specific disease and may be able to predict the prognosis and guide clinical decision making ( 37 ). Accuracy, precision, high sensitivity and specificity and low intra-individual variability are important characteristics of an ideal biomarker ( 36 ).…”
Section: Novel Nutritional Biomarkers Of Non-communicable Diseasesmentioning
confidence: 99%
“…Recent advances in functional magnetic resonance imaging (fMRI) approaches have provided a non-invasive method for characterization of central nervous system changes in some specific brain regions in PD (Mitchell et al, 2021), including the basal ganglia (Szewczyk-Krolikowski et al, 2014;Rolinski et al, 2015;Filyushkina et al, 2019), hippocampus (Zeng et al, 2017;Guo et al, 2021), cingulate gyrus (Zhang et al, 2017;Wang et al, 2021), and so on. Zhang et al (2017) found that patients with PD and fatigue had amplitude of low-frequency fluctuation (ALFF) changes in the right middle frontal gyrus within the attention network and in the left insula as well as right middle cingulate gyrus within the salience network.…”
Section: Introductionmentioning
confidence: 99%